A case of nephrocolic fistula presenting primarily with changes in bowel habits - Yuzhi Wan; Feng Xiao; Jiang Wu; Chaowu Chen (Urology Case Reports)
We report a rare case of nephrocolic fistula in a 56-year-old female presenting with a three-month history of altered bowel habits. Initial colonoscopy revealed a sinus tract in the descending colon. Her hemoglobin was 79 g/L, and she had a history of nephrolithiasis and trauma. Further imaging, including CT and contrast studies, confirmed a nephrocolic fistula. Surgical intervention involved left hemicolectomy, excision of the fistula tract, and renal repair. This case highlights the importance of considering nephrocolic fistula in patients with gastrointestinal symptoms and a history of urinary tract pathology.